(3fgGjI GdCQH aj afhf GdCOHs - (3GdfhjQj , CMeO Hf YHO GdhgGH Hf eMeO Hf YHO GdOGFe GdbQTj, TgGH GdOjf,J (B733 (3g` s ((3CMeO Hf Ydi GdXgjQ GdJfGSN s)
(3ChdgG (B:s
(3hHYO aef Chdi eG JOHLJ Hg GdWQhS hGdOaGJQ , hfWbJ HI BdSfI GdBbdGe Yf CahGg GdeMGjQ s
(3BNQgG (B:s
(3fSH GdfHi (B((3U(B) s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B165 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B306s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B106 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs